(untitled) (Annals of Medical Research, 2021)
Melkersson–Rosenthal syndrome (MRS) is a rare neuromucocutaneous syndrome. It is a rare orofacial granulomatosis of controversial etiology, marked by the triad of recurrent nonpitting orofacial edema, recurrent facial palsy and plicated tongue. Through two clinical cases, we present in this article the clinical features and the diagnostic approach that clinicians should follow when faced with this pathology.